Standardization of Screen Sizes for French bean Seed Processing¹ - VISHWANATH. K; KALAPPA V.P.; S. RAJENDRA PRASAD (Seed Research, 2026)
An attempt was made to standardize the screen size for grading French bean varieties viz., Arka Komal and Burpee Stringless. About 17 to 18 per cent more good seeds could be saved in Arka Komal by replacing the present recommended screen size 4.75 mm (s) by 4.50 mm (s). For Burpee Stringless seeds, present recommended screen size 4.75 mm (s) can be continued. Seed quality parameters viz., 100-seed weight, germination, field emergence, seedling length, vigour index were found to improve significantly with increase in sieve size in both the varieties at marginal expense of processing recovery. Investigation reveals the need for revision of screen size for grading of French bean varieties in order to minimize the processing loss and to meet the demand for good quality seeds for farming community.